Faktor-Faktor Yang Mempengaruhi Penyusunan Anggaran Pendapatan Dan Belanja Daerah Kabupaten Buton Tengah - Kasim, Kasim; Ramadhan, Syahril; Abidin, Zainul (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study aims to describe the factors that influence the preparation of the Regional Budget of the Central Buton Regency Government. This research uses a descriptive method with a qualitative approach. Data were collected using interview, observation and documentation techniques. The results showed that the leadership style carried out by the head of the regional apparatus organization was very influential in designing, planning and selecting programs related to the needs of the agency. The success of budgeting is also determined by administrative improvement factors, including the use of performance-based budget measurement instruments. The reward factor given by the Central Buton Regency Government to planners who excel in their duties and responsibilities can have a positive influence on competition and performance in budget preparation. Finally, the provision of sanctions for agencies that do not implement performance-based budgeting also motivates employees in the budget preparation process.